Implementasi Akad Wakalah Bil Ujroh dalam Transaksi Marketplace pada Mahasiswa Santri An-Nawawi Berjan Purworejo - Soleha, Siti Nur; Nursobah, Achmad; Ma’rufi, Anwar (AL-SULTHANIYAH, 2025)
The advancement of digital technology has driven significant transformation in the economic sector, including trade through marketplaces, which offer transaction efficiency. This study examines the understanding and implementation of the Wakalah bil ujroh contract among students of An-Nawawi Berjan, Purworejo, who have a background in Islamic education and whose activities are not far behind digital applications. With a qualitative descriptive-analytical approach, data were obtained through interviews, observations, documentation, and literature reviews related to Islamic law. The analysis shows that the Wakalah bil ujroh contract is implemented by fulfilling the pillars and requirements of sharia, such as the legal capacity of the parties involved, clarity of ijab-qabul, halal transaction objects, and agreements regarding ujrah, accompanied by high values of trust and accountability. Although there are technical obstacles such as differences in perception regarding the nominal ujrah, the implementation of this contract reflects a good understanding of sharia principles in digital transactions. This research contributes to the literature on Islamic economic law and offers practical guidance for Muslim communities to integrate sharia values into the digital economy.